2022
DOI: 10.3389/fgene.2022.965816
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of P4HB as a novel autophagy-related biomarker in diabetic nephropathy

Abstract: Diabetic nephropathy (DN), a frequent microvascular complication of diabetes, has been recognized as a primary cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD). Previous studies found that autophagy of renal tubular epithelial cells plays an important role in DN pathogenesis. Our research aimed to investigate the differentially expressed autophagy-related genes (DEARGs) between DN and healthy renal tubule samples and identify a novel autophagy-related biomarker associated with tubuloint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Through differential expression analysis and WGCNA, we obtained 14 autophagy-related key genes. Functional enrichment analysis further confirmed that these Frontiers in Cell and Developmental Biology frontiersin.org nephropathy, pulmonary hypertension, dermatomyositis, and rheumatoid arthritis (Du et al, 2020;Tong et al, 2021;Bai et al, 2022;Fan et al, 2022;Wang et al, 2022;Yang et al, 2022;Zhang et al, 2022). Therefore, ROC curve and survival analysis were performed on key genes to explore their diagnostic efficacy and prognostic value in sepsis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Through differential expression analysis and WGCNA, we obtained 14 autophagy-related key genes. Functional enrichment analysis further confirmed that these Frontiers in Cell and Developmental Biology frontiersin.org nephropathy, pulmonary hypertension, dermatomyositis, and rheumatoid arthritis (Du et al, 2020;Tong et al, 2021;Bai et al, 2022;Fan et al, 2022;Wang et al, 2022;Yang et al, 2022;Zhang et al, 2022). Therefore, ROC curve and survival analysis were performed on key genes to explore their diagnostic efficacy and prognostic value in sepsis.…”
Section: Discussionmentioning
confidence: 78%
“…ARGs have been shown to be of great value in the diagnosis and/or prognostic evaluation of diseases such as cancer, dilated cardiomyopathy, acute myocardial infarction, diabetic nephropathy, pulmonary hypertension, dermatomyositis, and rheumatoid arthritis ( Du et al, 2020 ; Tong et al, 2021 ; Bai et al, 2022 ; Fan et al, 2022 ; Wang et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2022 ). Therefore, ROC curve and survival analysis were performed on key genes to explore their diagnostic efficacy and prognostic value in sepsis.…”
Section: Discussionmentioning
confidence: 99%